Brand Image: Theoretical Development and Practical Applications - Yahya, Amri; Nuryakin; Handayani, Siti Dyah (Asian Journal of Management Analytics, 2024)
This research presents an in-depth analysis of research on brand image using a bibliometric approach. This research was conducted by detailing the findings from 364 documents published between 2018 and 2024 in the business sector. The analysis uses descriptive analysis of data from Scopus and VosViewer. The research results show that there is a collaboration between authors, which reflects a cross-disciplinary perspective.. Subject analysis shows a primary focus on Business Management (56.1%), while the inclusion of Social Sciences (11.7%), Decision Sciences (6,296%), and Economics (IL196%) reinforce the cross-disciplinary nature of the research. Trends over time show increasing interest in brand image, reflecting ongoing research into the theme of brand image.